2019
DOI: 10.1007/s40333-019-0005-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of three types of soil amendments on yield and soil nitrogen balance of maize-wheat rotation system in the Hetao Irrigation Area, China

Abstract: Excessive fertilization combined with unreasonable irrigation in farmland of the Hetao Irrigation Area (HIR), China, has resulted in a large amount of nitrogen (N) losses and agricultural non-point source pollution. Application of soil amendments has become one of the important strategies for reducing N losses of farmland. However, there is still no systematic study on the effects of various soil amendments on N losses in the HIR. In this study, three types of soil amendments (biochar, bentonite and polyacryla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Negative value of greenhouse gas N 2 O emissions: The negative value of the cultivated land ecosystem produced by the use of chemical fertilizers: As a result of the low utilization rate for chemical fertilizers, the unused part accumulates or migrates into the soil over time, causing a large amount of nitrogen loss and non-point-source agricultural pollution [42][43][44]. The negative value of unused fertilizers is calculated as follows:…”
Section: Ecological Benefit Calculation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Negative value of greenhouse gas N 2 O emissions: The negative value of the cultivated land ecosystem produced by the use of chemical fertilizers: As a result of the low utilization rate for chemical fertilizers, the unused part accumulates or migrates into the soil over time, causing a large amount of nitrogen loss and non-point-source agricultural pollution [42][43][44]. The negative value of unused fertilizers is calculated as follows:…”
Section: Ecological Benefit Calculation Methodsmentioning
confidence: 99%
“…The value of farmland environmental pollution caused by chemical fertilizers and plastic films exceeds the value of basic services to the farmland ecosystem, which increases farmland productivity to a certain extent but also aggravates the carrying load of the farmland ecosystem [20]. Simultaneously, excessive wasteland reclamation by humans causes damage to the service function value of the original desert ecosystems, such as value associated with raw salt production, water conservation, and climate regulation [42]. The measures of returning land and reducing water have not only reduced the unreasonable use of water resources and the pollution of farmland ecological environments, but also played a positive role in reducing greenhouse gas emissions.…”
Section: Eco-environmental Benefit Analysismentioning
confidence: 99%
“…The application of water-retaining agents and soil amendments have positive effects on improving soil structure and maintains soil water, gas and heat, finally enhancing the soil water-holding capacity [9][10][11]. For example, Wu et al showed that the application of soil amendments reduced field N losses by improving the physical structure of the soil, ultimately increasing the yield of wheat and maize [12]. The application of straw and plastic film mulching greatly inhibits soil water evaporation, which is beneficial to increase the water use efficiency [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%